(untitled) (Journal of actual problems of jurisprudence, 2026)
This article provides a comprehensive analysis of the impact of digitalization on the quality of proof in criminal cases, with a focus on procedural risks that may arise in this process from the perspective of forensic expertology. The article also substantiates a classification of the principles of digitalization of forensic examination as specific (private) theories that may be applied both to the general procedure of expert research and to particular types of forensic examinations. The study examines the legal and criminalistic significance of digital trace analysis within forensic practice, paying special attention to the mechanisms of their formation, their evidentiary value, as well as issues related to the classification of digital traces and information carriers as objects of forensic examination. Special attention is given to the problems of algorithmization and digitalization of forensic methods, including the use of artificial intelligence and neural networks. It is demonstrated that the introduction of digital technologies leads to significant changes in traditional approaches to the development of expert methodologies and, while influencing the quality of proof, may also become a source of certain procedural risks. The scientific significance of the study lies in the theoretical rethinking of the evidentiary status of expert conclusions in the context of the digitalization of forensic examination, as well as in its contribution to the development of specific theories of forensic expertology. The practical significance of the research consists in the possibility of applying the obtained results to improve the legal regulation of forensic expert activity, develop expert methodologies, and reduce procedural risks arising in the conduct of digital forensic examinations. Keywords: forensic examination, digitalization, expert opinion, quality of proof, procedural risks, proofs.